Perforation of the Duodenum by an Inferior Vena Cava Filter: a Potential Long-Term Complication in the Medical Device Era - Bretón, Carlos (2023)
The perforation of the duodenum is a rare complication of inferior vena cava (IVC) filter placement. The aim of this report is to highlight the importance of high clinical suspicion in patients with a history of IVC filter placement and non-specific abdominal pain. This report presents a case of a 62-year-old male with 8 years of right upper quadrant abdominal pain, who had a history of multiple deep vein thrombosis with IVC filter placement. Upper gastrointestinal endoscopy and angiotomography were used for diagnosis. An exploratory laparotomy was performed for removal of the IVC filter and repair of the vena cava and duodenum. The patient made satisfactory recovery and was discharged from the hospital a few days later. This case highlights the importance of timely diagnosis and treatment to reduce the risk of morbidity and mortality. It also suggests that patients with this complication may have a favorable outcome if the diagnosis is made early and appropriate surgical management is provided.